THE EFFECTIVENESS OF GROUP GUIDANCE SERVICES WITH THE JOYFUL LEARNING METHOD TO IMPROVE CHILDREN'S CREATIVITY AT THE CERIA LEARNING HOUSE IN PALEMBANG - leni marlina, Nanda putri islami; Manah Rasmanah,M.Si; Bela Janare Putra (Jurnal At-Taujih, 2026)
This study is entitled "The Effectiveness of Group Guidance Services with the Joyful Learning Method to Increase the Creativity of Children at the Palembang Cheerful Learning House" The purpose of this study is to determine the effectiveness of group guidance services with the joyful learning method to increase the creativity of children at the Palembang Cheerful Learning House. This study uses a quantitative approach with an experimental type of sample taken totaling 15 children. The sampling technique used is purposive sampling technique, namely a non-random sampling method carried out with certain criteria. Data collection techniques use questionnaires or questionnaires with a total of 40 statements, with the basis for decision making rCount > rTable then the statement is declared valid. The data analysis technique uses the Wilcoxon test to measure the significant difference between two populations based on the value (asymp.sig (2-tailed) < then HO is rejected and Ha is accepted. The results of this study indicate that the average pre-test before M (SD) 63, (13) With a low category of 11, medium 4, and high 0 becomes after the post-test M (SD) 101 (33) with a low category of 0, medium category 0, high category 15 experiencing an increase in creativity in children. Based on the results of the Wilcoxon test with a significance value of 0.001 < 0.05 from the Z score of -3.408, therefore group guidance with the joyful learning method is effective in increasing children's creativity at the Palembang cheerful learning house